Positive and Monotone Systems in a Partially Ordered Space - Mazko, A. G. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We investigate properties of positive and monotone differential systems with respect to a given cone in the phase space. We formulate criteria for the stability of linear positive systems in terms of monotonically invertible operators and develop methods for the comparison of systems in a partially ordered space.